On-Chain Verifiable Credential with Applications in Education - Nopporn Chotikakamthorn; Aye Mi San; Chanboon Sathitwiriyawong (ECTI Transactions on Computer and Information Technology (ECTI-CIT), 2024)
A verifiable credential (VC) has been standardized and applied in various domains, including education. Due to its immutability, blockchain has been considered and used for credential issuance and verification. Most existing methods, however, are not compatible with the W3C VC standard. In this paper, an on-chain VC issuance and verification method has been described. The method is based on the standard VC data model and applicable to any credential type. It decomposes a VC document into a VC template and the corresponding value array(s). This allows a VC to be issued on-chain in the Bitcoin BTC network, which has a limited data embedding capacity. The proposed method reduces blockchain resource consumption due to the reusability of a VC template. In addition, it allows the use of a concise VC fingerprint format instead of a full VC for credential exchange. Two issuance modes, namely the full on-chain and partial on-chain, are proposed targeting different use cases. The proposed method has been applied for issuing and verifying two learning credential types. The method was evaluated on the Bitcoin Testnet to measure time and space complexities. With the reduced-size VC fingerprint, the proposed method can embed a VC on a traditional paper-based credential as a compact-sized QR code. The proposed method offered faster VC issuance and verification than an existing standard-based verifiable credential method.
Keywords: Blockchain Technology Applications and Security; IoT and Edge/Fog Computing; Cryptography and Data Security